Prospective Observational Study of High-Dose Carbon-Ion Radiotherapy for Pelvic Recurrence of Rectal Cancer (GUNMA 0801) - Shiba, Shintaro (Front Oncol, 2019)
Background and purpose: Favorable clinical outcomes of carbon-ion radiotherapy for pelvic recurrence of rectal cancer have been described by previous prospective phase I/II and II studies; however, these studies were performed at a single institution. Therefore, we conducted a prospective observational study aimed at exploring whether carbon-ion radiotherapy for post-operative pelvic recurrence of rectal cancer provides a less invasive local treatment strategy with higher cure rates than other anticancer treatments. Materials and methods: Patients (1) with pelvic recurrence of rectal cancer, as confirmed by histology or diagnostic imaging; (2) without distant metastasis; (3) who had undergone curative resection of their primary disease and regional lymph nodes, without gross or microscopic residual disease; and (4) with radiographically measurable tumors were included in this study. The total carbon-ion radiotherapy dose for all patients was 73.6 Gy [relative biological effectiveness (RBE)] administered in 16 fractions once daily for 4 days a week (Tuesday to Friday). Results: A total of 28 patients were enrolled between October 2011 and July 2017. The median follow-up duration was 38.9 months. The 3-year overall survival, local control, and progression-free survival rates were 92, 86, and 31%, respectively. At the time of the analysis, 4 patients had local recurrence, and 7 had died of rectal cancer. None of the patients developed grade 3 or higher acute toxicities. Late toxicities occurred in 2 and 7 patients who developed grade 3 pelvic infection and grade 2 peripheral neuropathy, respectively. Conclusion: Carbon-ion radiotherapy for pelvic recurrence of rectal cancer showed favorable clinical outcomes and is a highly curative and less invasive local treatment.